Draft Genome Sequence of Pseudomonas sp. Strain CCA1, Isolated from Leaf Soil - Akita, Hironaga (Genome Announc, 2016)
Pseudomonas sp. strain CCA1 was isolated from leaf soil collected in Higashi-Hiroshima City in Hiroshima Prefecture, Japan. Here, we present a draft genome sequence of this strain. The genome consists of 24 contigs for a total of 6,993,992 bp, 8,917 predicted coding sequences, and a GC content of 67.2%.